Evaluación de diferentes dosis de silicio en el cultivo de banano (Musa acuminata L.) para el control de Sigatoka negra (Pseudocercospora fijiensis) - Pérez Jacome, Francisco Javier (2022)
Black sigatoka is considered the most destructive foliar disease and the most economically valuable in banana and plantain crops. It is caused by the ascomycete fungus Pseudocercospora fijiensis. The objective of this present investigation is to evaluate the effectiveness of different doses of silicon to control black sigatoka in banana cultivation. This product was applied in different doses to determine the most effective treatment.